Rosyjskie czasowniki ruchu wirowego w świetle metafory pojęciowej - Narloch, Andrzej (Studia Rossica Posnaniensia, 2019)
In recent years linguistic studies have laid great emphasis on the semantic side of linguistic expressions. The aim of this paper is to introduce and describe the term “circular motion” viewed from the perspective of the conceptual metaphor in Russian. It describes the process of creating such metaphors based on the notions of source and target domains.